Determinants of foreign direct investment inflows in Malaysia / Amilya Nazima Amirezal - Amirezal, Amilya Nazima (2014)
Recently, government of Malaysia is serious in transforming the economy and will continue to undertake proactive measures to promote FDIS to ensure Malaysia meet the target in 10th Malaysia Plan. Hence, the problem is to determine whether those variables involves can be classified as important factors in attracting and maintaining the interest of investors (foreign) to put their money in Malaysia. In the last 2 decades, foreign direct investment (FDI) flows have grown rapidly all over the world. This is because many countries and especially developing countries see FDI as an important element in their strategy for economic development